Notas corológicas del macrofitobentos de Andalucía (España). VI. - Altamirano, María; Díaz-Such, Blanca; García-Sánchez, Jose (Acta Botanica Malacitana, 2006)
New records for the macrophytobenthos of Andalusia (Spain). VI Palabras clave. Acrochaetium codii, Andalucía, Ceramium echionotum var. mediterraneum, corología, macroalgas marinas, Taonia atomaria f. ciliata. Key words. Acrochaetium codii, Andalusia, Ceramium echionotum var. mediterraneum, geographical distribution, seaweeds, Taonia atomaria f. ciliata.